Antecedents of Market Orientation and its impact on Customer-Oriented Behavior: the moderating role of Job Satisfaction for Health care Professionals: A comparison of Public and Private Hospitals - Shafaqat, Sara; Muhammad Zia ur Rehman; Muhammad Abdur Rehman Khadam (Journal of Innovative Research in Management Sciences, 2021)
Purpose– The purpose of this study is to develop and test a model for Customer-oriented-behavior and Market-orientation that is based on Professionalism, Rewards, and Job-satisfaction. Design/methodology/approach – It was an empirical study that measured the hypothesized relationship among variables of research interest. By using a convenient sampling technique, data were collected from healthcare professionals of Pakistan. Findings – The results obtained have provided a cause-effect relationship of professionalism and rewards with Market-orientation concerning Customer-oriented-behavior of health professionals and personnel. A significant impact of variables: professionalism and rewards on market orientation and positive relationships of market- orientation with job satisfaction and customer-oriented behavior were observed. Research limitations/implications – The size of the sample used for the study may not allow the generalization of results. However, the study has motivated the author to increase the size of the sample for exploring the phenomenon in more detail. Practical implications – Health professionals and personnel require a comprehensive market orientation regarding how to satisfy their customers; this study has provided some sort of management in that perspective which may help businesses to lessen distance from their potential customers.